Structural and mechanistic investigations of protein S-glycosyltransferases. Issue 12 (16th December 2021) - Fujinami, Daisuke; Garcia de Gonzalo, Chantal V.; Biswas, Subhanip; Hao, Yue; Wang, Huan; Garg, Neha; Lukk, Tiit; Nair, Satish K.; van der Donk, Wilfred A.
Summary: Attachment of sugars to nitrogen and oxygen in peptides is ubiquitous in biology, but glycosylation of sulfur atoms has only been recently described. Here, we characterize two S -glycosyltransferases SunS and ThuS that selectively glycosylate one of five Cys residues in their substrate peptides; substitution of this Cys with Ser results in a strong decrease in glycosylation activity. Crystal structures of SunS and ThuS in complex with UDP-glucose or a derivative reveal an unusual architecture in which a glycosyltransferase type A (GTA) fold is decorated with additional domains to support homodimerization. Dimer formation creates an extended cavity for the substrate peptide, drawing functional analogy with O -glycosyltransferases involved in cell wall biosynthesis. This extended cavity contains a sharp bend that may explain the site selectivity of the glycosylation because the target Cys is in a Gly-rich stretch that can accommodate the bend. These studies establish a molecular framework for understanding the unusual S -glycosyltransferases. Graphical abstract: Highlights: The S -glycosyl transferases SunS and ThuS have a unique domain architecture The dimerization and tetratricopeptide repeat domains guide substrate recognition A pocket near the sugar donor explains the substrate tolerance of these enzymes A substrate binding groove explains the site selectivity of peptide glycosylation Abstract : Sulfur-linkages in glycopeptides increase their metabolic stability. These structures have been made by chemical synthesis or engineered enzymes. Fujinami et al. present crystal structures and mutagenesis data of naturally occurring glycosyltransferases that make antimicrobial S -linked glycopeptides, thereby establishing a molecular framework for understanding these unusual enzymes.